Allogeneic hematopoietic stem cell transplantation for STAT3 hyper-IgE syndrome: a worldwide study - Christo Tsilifis; Johannes Raedler; Joanna Renke; Michael Medinger; Alexandra Laberko; Ásgeir Haraldsson; Niraj Patel; Peter Ciznar; Melanie Wong; Steven J. Keogh; Paul Gray; Richard Mitchell; et al. (Blood Advances)
Abstract: Signal transduction and activator of transcription 3 hyperimmunoglobulin E syndrome (STAT3-HIES) is a multisystem disorder causing recurrent skin and respiratory infection with bronchiectasis, pneumatoceles, and aspergillosis; lymphoma; and extraimmune manifestations including fractures and vasculopathy. Published data on immune and extraimmune hematopoietic stem cell transplant (HSCT) outcomes focus on case reports or small cohorts. We conducted an international multicenter retrospective study of HSCT in STAT3-HIES. Primary end points were overall survival (OS) and event-free survival (EFS; events were death, graft failure, chronic graft-versus-host disease [GVHD]). We identified 41 patients over a 28-year period. HSCT indication was infection (93%) or lymphoma (7%). Median age at HSCT was 14 years (range, 4-45). Most patients had pre-HSCT respiratory disease (93%), including parenchymal lung disease (68%), and prior suspected/confirmed pulmonary fungal infection (32%). Patients received peripheral blood stem cells (51%) or marrow (49%) from HLA 10/10–matched unrelated donors (44%), matched family donors (44%), mismatched family donors (10%), or 1 9/10–mismatched unrelated donor (2%). Conditioning regimens were predominantly treosulfan-based (59%; with thiotepa, 34%); other patients received busulfan-based (24%) or melphalan-based (17%) regimens. Median follow-up for surviving patients was 5 years (0.8-28). The 5-year OS was 93%, and 5-year EFS 90%. Cumulative incidence of grade 2 to 4 acute GVHD was 22%. Median whole blood donor chimerism at latest follow-up was 100%. Eighty-seven percent of patients have reduced or no bacterial or fungal respiratory infection. After HSCT, 20% developed new skeletal fractures. This worldwide study expanded data on HSCT for STAT3-HIES to 41 patients; despite significant pre-HSCT pulmonary morbidity, OS was high, and patients have improved skin and respiratory disease though the impact on extraimmune manifestations appears limited.